Energy Characteristics in the Flow Channel of the Shaft-Type Tubular Pumping Station Considering Tides - Yufan He; Can Luo; Li Cheng; Yandong Gu; Bin Gu (Journal of Marine Science and Engineering, 2024)
The shaft-type tubular pumping station has the remarkable characteristics of a large flow rate and high efficiency. It can realize the functions of irrigation, pumping, and drainage through pumping and generating conditions considering tides. Moreover, it is widely used in the plain area of eastern China and the tidal area along the marine region. Due to the different topological features of the airfoil of the impeller, the energy evolution characteristics of the shaft-type tubular pumping station during pumping and generating conditions remain unclear. The entropy generation theory was introduced to numerically simulate the flow pattern and energy characteristics in the shaft-type channel, impeller, and straight channel in operation conditions. The results show that the flow pattern is stable when the shaft-type channel and the straight-type channel are used as the inlet channel under pumping and generating conditions, and a low-pressure region occurs in the contraction section of the shaft-type channel. The velocity of sections of the inlet and outlet and the middle section of the impeller in the generating condition is larger than that in the pumping condition. In addition, the difference in the static pressure on the blade surface nearby the hub is large. With a change in the position of the wingspan, the difference gradually decreases from the small flow condition to the large flow condition. There is a high-entropy production rate zone in the channel contraction section and the shaft-type wall surface of the shaft-type flow channel. When the straight-type channel is used as the outlet flow channel, a high-entropy production region appears near the inlet water surface. In the pumping condition, a high-entropy production area is found at the inlet of the impeller, the blade groove channel, and the inlet of the guide vane. In the generating condition, a high-entropy production area is found at the out-of-impeller outlet, the blade groove channel, and the outlet of the guide vane. These research achievements have some reference value for the design of the shaft-type tubular pumping station considering tides and the study of hydraulic performance, along with the energy characteristics of the channels.